Internationalization in the Global Pandemic Era 2020-21 Challenges, Innovations and Way Forward - Chan Chee Ming; Dr. Yong Zulina Zubairi (Penerbit UTHM, 2023)
During the height of the challenging times of COVID-19 pandemic, I was devastated as my plans in driving internationalization university-wide was heavily disrupted. Student exchanges and international travel came to a complete halt and in most a total chaos. Things suddenly brightened up when the International Office of UTHM, reached out to us and came up with a brilliant idea to pen our thoughts and personal reflections as we experienced tectonic shifts in our social and personal lives. It was a powerful time of healing, of deep personal reflection on who we are, where we have been, and where we are heading. Living amid these challenging times, has made us deeply aware and grateful for things that we have taken for granted, appreciating friends and support we have and mindful of the reality unfolding before us. Together we began to collaborate and actively look for solutions. The collections of essays are evidence of how we have found the inner strength to be able to adapt, to innovate, to reinvent and imagine how internationalization will look like in the future.